Analysis of Work Injuries and Health Complaints Among Farmers in Bontomanai Village, Rumbia Subdistrict, Jeneponto Regency - Widiastuty, Lilis; Mallapiang, Fatmawaty; Ibrahim, Hasbi; Azwar, Muhammad (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Work in the agricultural sector heavily depends on nature and the physical environment. The risk of accidents increases due to fatigue, inadequate equipment, difficult terrain, exposure to extreme weather, and poor health, which are also associated with working and living in remote areas. This study aimed to identify the factors influencing injuries and health complaints among farmers in Bontomanai Village. This research is a quantitative study with a cross-sectional design conducted from July to October 2024 in Bontomanai Village, Gowa Regency. The respondents of this study were 315 farmers selected through purposive sampling. The independent variables were age, education level, gender, work experience, working hours, use of personal protective equipment (PPE), and working posture. A total of 16.5% of respondents experienced injuries, while 55.6% reported health complaints. There was a significant relationship between gender and injuries, as well as between working hours and health complaints. Limiting working hours and empowering the community by forming "Agricultural OHS Cadres" is suggested to provide continuous knowledge about Occupational Health and Safety (OHS) in the agricultural sector. Keywords: injury; farmer; health; safety